Influence of amide-containing side chains on the mechanical properties of diketopyrrolopyrrole-based polymers - Ocheje, Michael U.; Selivanova, Mariia; Zhang, Song; Van Nguyen, Thi Hai; Charron, Brynn P.; Chuang, Ching-Heng; Cheng, Yu-Hsuan; Billet, Blandine; Noori, Suendues; Chiu, Yu-Cheng; Gu, Xiaodan; Rondeau-Gagné, Simon (Polymer chemistry, 2018)
An efficient strategy to modulate the mechanical properties of conjugated polymers has been developed through the incorporation of amide-containing alkyl chains in diketopyrrolopyrrole-based conjugated polymers. The side-chain engineering performed with hydrogen bonding moieties (up to 20 mol% of amide-containing side-chains) was found to reduce the crystallinity of the conjugated polymers in the solid state. Interestingly, this reduction in crystallinity drastically influenced the mechanical properties of the new DPP-polymers, by promoting their stretching ability, reducing the elastic modulus of the polymers, and facilitating the molecular alignment after stretch. The resulting polymers with 10% hydrogen bonding side chains showed a maximum stretchability of 75% elongation, without the appearance of nanoscale cracks, and a detailed investigation of the mechanical properties was performed by a combination of morphological characterization tools, including grazing-incidence X-ray diffraction, polarized UV-Vis spectroscopy and optical/atomic force microscopy to support our finding. Additionally, incorporation of amide-containing side-chains also enabled the regeneration of the conjugated polymer morphology after damage. Our results demonstrate that the introduction of amide-containing alkyl chains is an effective strategy to enhance the mechanical properties of π-conjugated polymers without disrupting the π-conjugation, and to enable new properties such as morphological healing.